2019
DOI: 10.3390/met9121275
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Effective Heat Treatment Involving Intercritical Hardening for High Strength/High Elongation of 0.2C–3Al–(6–8.5)Mn–Fe TRIP Steels: Microstructural Evolution and Deformation Behavior

Abstract: High strength/high elongation continues to be the primary challenge and focus for medium-Mn steels. It is elucidated herein via critical experimental analysis that the cumulative contribution of transformation-induced plasticity (TRIP) and microstructural constituents governs high strength/high elongation in 0.2C–3Al–(6–8.5)Mn–Fe steels. This was enabled by an effective heat treatment involving a combination of intercritical hardening and tempering to obtain high strength/high ductility. An excellent combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The martensite in the microstructure was responsible for the low ductility [35]. Mou et al [36] found that lamellar austenite was more likely to cause stress relaxation during martensitic transformation, resulting in low plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The martensite in the microstructure was responsible for the low ductility [35]. Mou et al [36] found that lamellar austenite was more likely to cause stress relaxation during martensitic transformation, resulting in low plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were devoted toward understanding the factors that affect the stability of austenite, such as carbon content in austenite [27,28], austenite grain size [29,30], austenite morphology [30,31] and Schmidt factor [32,33], but studies on the degree of these factors are rare. From the above analysis, it can be seen that the hot-rolled steel A had an intense TRIP effect during deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of austenite stability increased the ultimate tensile strength and total elongation of TRIP steel [8]. Furthermore, Mou et al [9] found that lamellar austenite was more likely to cause stress relaxation during martensitic transformation, resulting in a discontinuous TRIP effect and thus higher ductility. Peng et al [10] carried out extension experiment at elevated temperature on Fe-22Mn-0.7C TWIP steel in the temperature range of 700-1250 • C and found that the reduction of area was extremely low, all below 40%.…”
Section: Introductionmentioning
confidence: 99%